HOXA1 is a radioresistance marker in multiple cancer types - He, Lu; Liang, Min; Guo, Weisheng; Liu, Jinquan; Yu, Yi (Frontiers in Oncology, 2022)
Radiotherapy is an important therapeutic method for patients with cancer. However, radioresistance can cause treatment failure. Thus, there is an urgent need to investigate mechanisms of radioresistance and identity markers that could be used to predict radioresistance and prognosis of post-radiotherapy cancer patients. In the present study, we propose HOXA1 as a candidate biomarker of intrinsic radioresistance in multiple cancer types. By analyzing data from The Cancer Genome Atlas (TCGA), we found that HOXA1 was aberrantly upregulated in multiple cancers, and that elevated HOXA1 was significantly associated with poor prognosis of post-radiotherapy head and neck squamous cell carcinoma (HNSCC) and low-grade glioma (LGG) patients. Correlation analysis showed that HOXA1 expression was positively correlated with expression of EGFR, CDK6, and CAV1, which have been reported to enhance radioresistance. In addition, gene set enrichment analysis (GSEA) showed that the oxidative phosphorylation gene set was negatively enriched in HOXA1 high-expression samples in both HNSCC and LGG. Moreover, immunohistochemical assays indicated that high HOXA1 expression was significantly correlated with a high recurrence rate of nasopharyngeal carcinoma (NPC) after radiotherapy. Further in vitro experiments demonstrated that HOXA1 knockdown markedly attenuated the DNA repair capacity of NPC cells and sensibilized NPC cells to irradiation. Taken together, the results of this study demonstrate that HOXA1 has potential to be a predictive marker for radioresistance and post-radiotherapy prognosis that could help to guide individualized treatment in multiple cancer types.